Role of NKCC1 Activity in Glioma K+ Homeostasis and Cell Growth: New Insights With the Bumetanide-Derivative STS66 - Luo, Lanxin; Wang, Jun; Ding, Dawei; Hasan, Md Nabiul; Yang, Sung-Sen; Lin, Shih-Hua; Schreppel, Philipp; Sun, Baoshan; Yin, Yan; Erker, Thomas; Sun, Dandan (Frontiers in Physiology, 2020)
Introduction: Na+-K+-2Cl- cotransporter isoform 1 (NKCC1) is important in regulating intracellular K+ and Cl- homeostasis and cell volume. In this study, we investigated role of NKCC1 in regulating glioma K+ influx and proliferation in response to apoptosis inducing chemotherapeutic drug temozolomide (TMZ). The efficacy of a new BMT-derivative NKCC1 inhibitor STS66 (3-(Butylamino)-2-phenoxy-5-[(2, 2, 2-trifluoroethylamino) methyl] benzenesulfonamide) in blocking NKCC1 activity was compared with well-established NKCC1 inhibitor bumetanide (BMT). Methods: NKCC1 activity in cultured mouse GL26 and SB28-GFP glioma cells was measured by Rb+ (K+) influx. The WNK1-SPAK/OSR1-NKCC1 signaling and AKT/ERK-mTOR signaling protein expression and activation were assessed by immunoblotting. Cell growth was determined by BrdU incorporation assay, MTT proliferation assay and cell cycle analysis. Impact of STS66 and BMT on cell Rb+ influx and growth was measured in glioma cells treated with or without TMZ. Results: Rb+ influx assay showed that 10 μM BMT markedly decreased the total Rb+ influx and no additional inhibition detected at > 10 μM BMT. In contrast, the maximum effects of STS66 on Rb+ influx inhibition were at 40-60 μM. Both BMT and STS66 reduced TMZ-mediated NKCC1 activation and protein upregulation. Glioma cell growth can be reduced by STS66. The most robust inhibition of glioma growth, cell cycle, and AKT/ERK signaling was achieved by the TMZ+STS66 treatment. Conclusion: The new BMT-derivative NKCC1 inhibitor STS66 is more effective than BMT in reducing glioma cell growth in part by inhibiting NKCC1-mediated K+ influx. TMZ+STS66 combination treatment reduces glioma cell growth via inhibiting cell cycle and AKT-ERK signaling.